Chiral Biomaterials for Nanomedicines: From Molecules to Supraparticles - Wookjin Jung; Junyoung Kwon; Wonjoon Cho; Jihyeon Yeom (Pharmaceutics, 2022)
Chirality, the property whereby an object or a system cannot be superimposed on its mirror image, prevails amongst nature over various scales. Especially in biology, numerous chiral building blocks and chiral-specific interactions are involved in many essential biological activities. Despite the prevalence of chirality in nature, it has been no longer than 70 years since the mechanisms of chiral-specific interactions drew scientific attention and began to be studied. Owing to the advent of chiral-sensitive equipment such as circular dichroism spectrometers or chiral liquid columns for chromatography, it has recently been possible to achieve a deeper understanding of the chiral-specific interactions and consequential impacts on the functionality and efficiency of nanomedicine. From this point of view, it is worthwhile to examine previously reported chiral biomaterials with their compositions and possible applications to achieve new paradigms of biomaterials. This review discusses chiral materials on various scales and their biological applications.